From disability to ability: comprehensive rehabilitation providing a holistic functional improvement in a child with neglected neural tube defect - Mishra, Kriti (BMJ Case Rep, 2017)
Neural Tube defects are one of the most common congenital disorders, presenting in a paediatric rehabilitation set-up. With its wide spectrum of clinical presentation and possible complications, the condition can significantly impact an individual’s functional capacity and quality of life. The condition also affects the family of the child leaving them with a lifelong impairment to cope up with. Through this 16-year-old child, we shed light on the effects of providing rehabilitation, even at a later stage and its benefits. We also get a glimpse of difficulties in availing rehabilitation services in developing countries and the need to reach out many more neglected children like him with good functional abilities.